2016
DOI: 10.7717/peerj.1699
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour and risk of sexually transmitted infections in young female healthcare students in Spain

Abstract: Background. Several authors have examined the risk for sexually transmitted infections (STI), but no study has yet analyzed it solely in relation with sexual behaviour in women. We analyzed the association of sexual behaviour with STI risk in female university students of healthcare sciences.Methods. We designed a cross-sectional study assessing over three months vaginal intercourse with a man. The study involved 175 female university students, without a stable partner, studying healthcare sciences in Spain. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
(25 reference statements)
0
12
0
1
Order By: Relevance
“…Authors reported psychological psychosexual disorders caused by FGM that could lead to decreased sexual desire [39][40][41]. In consequence, the sexual experience decrease, and probably the number of partners, so STI risk factors [42]. In addition, other authors reported that the women who have experienced FGM are generally from a conservative family environment that could contribute to reducing these risk factors of STI [43].…”
Section: Plos Onementioning
confidence: 99%
“…Authors reported psychological psychosexual disorders caused by FGM that could lead to decreased sexual desire [39][40][41]. In consequence, the sexual experience decrease, and probably the number of partners, so STI risk factors [42]. In addition, other authors reported that the women who have experienced FGM are generally from a conservative family environment that could contribute to reducing these risk factors of STI [43].…”
Section: Plos Onementioning
confidence: 99%
“…Based on other studies, it is seen that sexually transmitted infections (STIs) are diseases transmitted through sexual contact with clinical manifestations in the form of abnormalities, especially in the genitals. Failure of early detection of STIs can cause various complications such as pregnancy outside the womb, anogenital cancer, infection in newborns, or infection in pregnancy [6].…”
Section: A the Correlation Between Sexual Behavior And Complaints Onmentioning
confidence: 99%
“…Indeed, several situations leading to high-risk sex in other groups have been reported, for example within the military [26], during travels abroad [27], during adolescence, in correctional facilities or community facilities [28] or for female sex workers in particular in low-income countries [29], which may provide a setting for HIV and bacterial STI transmission. Among young female healthcare students, 29.7% were assessed as being at risk of STIs in Spain [30]. Changes in sexual practices are demonstrated by a study on Swedish students, whose number of sexual partners had increased over the last 25 years, while their use of condoms decreased [31].…”
Section: What Is the Target Population For Bacterial Prep?mentioning
confidence: 99%